Analisis Pengetahuan Wajib Pajak Terhadap Pemenuhan Kewajiban Perpajakan UMKM : Sebuah Studi Pemetaan Sistematis - Wahyu Sinta Eliysabet; Safri Nurmantu; Resista Vikaliana (IKRA-ITH HUMANIORA : Jurnal Sosial dan Humaniora, 2022)
This study aims to identify and analyze the knowledge of taxpayers on the fulfillment of taxationobligations of MSMEs by using a systematic mapping study method to examine the scientificpublications of taxpayers' knowledge on the fulfillment of MSME Taxation Obligations produced fromtime to time, the focus and types of research that are most investigated, browse 134 (one hundred andthirty four) articles based on the topic areas studied under the category of Taxation Regulations,Taxpayer Compliance, Implementation of PP No. 46 of 2013 and the implementation of PP No. 23 of2018 were later reduced to 50 (fifty) articles that focused on qualitative and quantitative researchmethods and types of research, namely validation research, evaluation research, solution proposals,philosophical papers and experience papers. The results of this study use the theory of mardiasmoand chatarina which suggest three criteria in the knowledge of tax obligations, understanding ofMSME tax regulations, and compliance in implementing MSME tax obligations so that it shows thatunderstanding of taxpayer knowledge on the fulfillment of UMKM tax obligations has a positive effecton MSME taxpayer compliance because the higher the level of understanding of the taxationknowledge of UMKM, the higher the compliance of the UMKM taxpayers